Design and manufacturing of a human standardised hip cup out of titanium: Konstruktion und Fertigung einer menschlichen standardisierten Hüftpfannenprothese aus Titan. Issue 7 (5th July 2016) - Behrens, B. A.; Escobar, S. B.; Niemeier, H.; Vucetic, M.; Bouguecha, A.; Lucas, K.; Nolte, I.; Wefstaedt, P.; Lerch, M.; Stukenborg‐Colsman, C.; Almohallami, A.
Abstract : Background: In recent years, the use of hip prostheses has become a routine procedure. Despite this experience and good clinical results different complications arise which have a negative influence on the lifetime of prostheses. Especially the migration or loosening of the hip cup prosthesis due to strain adaptive bone remodelling is still a problem. Patient‐individual prostheses represent a possible solution to this problem. Individual hip cups, however, are just implanted for the treatment of massive deformities or tumours. This study aimed at developing an innovative concept for the production of patient‐specific human hip prostheses made of titanium plates by sheet metal forming. Methods: For the realisation of this innovative concept, a reproducible design method for the generation of standardised human hip cup prosthesis was generated based on 13 original human geometries. By means of this methodology a hip cup was designed. Based on this design a human hip cup was produced by a developed high‐pressure sheet metal forming process. The development of the process was accompanied by a numerical preliminary design. Results: A comparison between the simulation and the fabricated hip cup leads to a standard deviation of 0.404 mm. Furthermore, an implantation of the prosthesis in a synthetic bone model shows a satisfactory fit accuracy at the edge of the prosthesis. Conclusion: The high‐pressure sheet metal forming process is suitable to manufacture the designed standardised hip cup. However, further optimisation is necessary.